A Rare Localization of Actinomycosis Mimicking Ulcerative Malignancy. (4th March 2013) - Volpi, Luca; Ferreli, Fabio; Bignami, Maurizio; Pistochini, Andrea; Meloni, Francesco; Karligkiotis, Apostolos; Castelnuovo, Paolo
Abstract : Actinomycosis is a chronic, suppurative, and granulomatous process caused by Actinomycetes, saprophytic bacteria normally residing in the oral cavity. It can involve any organ, but the cervicofacial disease is the most frequent. Pharyngolayngeal involvement is rare and usually occurs secondary to the oral or cervical disease. There are few cases of primary pharyngolaringeal actinomycosis described in the literature. A rare case of pharyngeal actinomycosis mimicking an ulcerative malignancy in a 63-year-old man is reported. The patient was treated successfully with long-term antibiotic therapy. The clinical and pathological features and the aspects of diagnosis and treatment of cervicofacial actinomycosis are discussed.